PENGARUH KUALITAS PELAYANAN KESEHATAN DAN KEPUASAN PASIEN TERHADAP CITRA KLINIK “X” DI TUBAN - Andrianto, Andrianto; Sasmito, Cahyo; Indragunawan, Cakti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
This study aims to determine and analyze the effect of service quality and patient satisfaction on X Tuban clinical image. Sampling is done by simple random sampling. The number of samples determined was 92 samples. The data used are primary data and secondary data. The analytical method used to determine the effect of service quality and patient satisfaction on the X Tuban Clinic image is multiple linear regression with the Ordinary Least Square (OLS) method. Before a regression is carried out, a validity and reliability test is performed for each question. In addition, a normality test and a classic assumption test are performed. The results showed that the quality of service and patient satisfaction simultaneously and individually affected the positive image of the Tuban X Clinic.